Influence of integrated nutrient management on growth and yield of wheat (Triticum aestivum L.) under irrigated conditions - SINGH, BABLU; KAUR, VEERPAL; BABLI; SAINI, SAT PAL (Journal of Soil and Water Conservation, 2023)
An experiment was carried out to study the influence of integrated nutrient management on growth and yield of wheat (Triticum aestivum L.) under irrigated conditions” at Research Farm Department of Agriculture, Baba Farid College, Bathinda, during Rabi 2018–19. The experiment was laid out in randomized block design with three replication and ten treatments viz. T1 (Control), T2 (50% RDN through urea), T3 (75% RDN through urea), T4 (100% RDN through urea), T5 (50% RDN through urea + 10 t ha- 1FYM), T6 (75% RDN through urea + 10 t ha-1 FYM), T7 (100% RDN through urea 10 t ha-1 FYM), T8 (50% RDN through urea + 10 t ha-1 Vermicompost) T9 (75% RDN through urea + 10 t ha-1 Vermicompost) and T10 (100% RDN through urea + 10 t ha-1 Vermicompost). The highest yield attributes and yield of wheat was produced with application of 100% RDN through urea 10 t ha-1 FYM but it did not differ significantly with application of100% RDN through urea + 10 t ha-1 Vermicompost was applied. T10 produced 94.96 percent higher number effective tillers, 34.14 percent taller spike length, 25.47 percent more test weight, 165.21 per cent higher grain yield and157.13 percent higher straw yield of wheat over control.